2019
DOI: 10.1080/2162402x.2019.1629260
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA expression patterns are associated with tumor mutational burden in lung adenocarcinoma

Abstract: Background: Tumor mutational burden (TMB) has emerged as an independent biomarker to predict patient responses to treatment with immune checkpoint inhibitors (ICIs) for lung adenocarcinoma (LUAD). MicroRNAs (miRNAs) have a crucial role in the regulation of anticancer immune responses, but the association of miRNA expression patterns and TMB is not clear in LUAD. Methods: Differentially expressed miRNAs in samples with high TMB and low TMB samples were screened in the LUAD dataset in The Cancer Genome Atlas. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…We obtained tumor mutation data of LUAD from TCGA database. 10 mutations per megabyte (MB) was used as the threshold of high and low TMB ( Hellmann et al, 2018 ; Lv et al, 2019 ). A high TMB level was defined as >10 mutations per MB, and below that threshold was a low TMB level.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained tumor mutation data of LUAD from TCGA database. 10 mutations per megabyte (MB) was used as the threshold of high and low TMB ( Hellmann et al, 2018 ; Lv et al, 2019 ). A high TMB level was defined as >10 mutations per MB, and below that threshold was a low TMB level.…”
Section: Methodsmentioning
confidence: 99%
“…miRNAs expression in the tumor microenvironment plays a crucial role in mediating and controlling several immune and cell interactions, and convolute in the regulation of immune checkpoints, PD1 and PD-L1 [63]. It was reported that a 25 miRNA-based signature classi er could predict the TMB level with high accuracy [64]. A cluster of highly expressed miRNA including hsa-miR-492, hsa-miR-498, hsa-miR-320 were found to be correlated with tumorigenesis of retinoblastoma [65].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a significant association between somatic RYR2 (ryanodine receptor 2) mutations and high TMB was defined as a potential prognostic marker for lung adenocarcinoma [9]. Other authors have developed a 25 miRNA-based signature classifier, involved in immune-related biological processes and in cancer-related pathways, as a potential biomarker to predict TMB levels in lung adenocarcinoma [10]. High TMB can increase neo-antigen expression linked to T-cell recruitment [4].…”
Section: -Update On Predictive Biomarkers For Ici and Emerging Novmentioning
confidence: 99%